Losartan hydroxylation phenotype in an Ecuadorian population: influence of CYP2C9 genetic polymorphism, habits and gender. (November 2012) - Dorado, Pedro; Beltrán, Leonardo J; Machín, Esther; Peñas-LLedó, Eva M; Terán, Enrique; LLerena, Adrián
Aim: To describe for the first time CYP2C9 hydroxylation phenotype with CYP2C9 genotypes in a Hispanic (Ecuadorian) population using losartan; and the relevance of gender, tobacco, ethanol and caffeine consumption on the enzyme hydroxylation capacity.Methods: Ecuadorian healthy volunteers (n = 194) received a single oral dose of 25 mg losartan. Losartan metabolic ratio was defined as losartan:E3174 concentration. CYP2C9 alleles *2, *3, *4, *5 and *6 were analyzed.Results: No phenotypically poor metabolizers were found. The metabolic ratio (mean ± standard deviation) was higher (p < 0.05) in CYP2C9*1/*3 carriers (12.4 ± 13.8; n = 6) versus CYP2C9*1/*1 (4.9 ± 7.0; n = 167), as well as in females versus males (6.72 ± 9.72 and 3.76 ± 4.48, respectively; p < 0.05). Only the following genotypes, CYP2C9*1/*1, CYP2C9*1/*2 and CYP2C9*1/*3, were found with a frequency of 86.1%, 10.8% and 3.1%, respectively.Conclusion: Despite the mean metabolic ratio being higher in this population than in others previously studied across genotypes, no poor metabolizers, either phenotypically or genotypically, were found. Original submitted 21 August 2012; Revision submitted 21 September 2012